PERAN HUMAS DALAM KETERBUKAAN INFORMASI PUBLIK DI UNIVERSITAS BENGKULU - Naga Tondi Hasibuan (Jurnal Komunikasi dan Budaya, 2021)
The objective of this research was to provide an overview of the role of Public Relations at University of Bengkulu for implementing UU No. 14, 2008 on the openness of Public Information. To saw this role, this research used four public relations roles according to Dozier and James these were as an expert prescriber, communication facilitator, problem solving process facilitator and technician facilitator. This research used the descriptive studies with qualitative data obtained by conducted in-depth interviews, field observations and also used the literature studies. The results of this descriptive research was illustrated that the Public Relations of University of Bengkulu only plays one role. That is as a technician facilitator and the other roles of the public relations such as Expert Prescriber, problem solving process facilitator, and Communication facilitator were played by PPID (Information and Documentation Management Officer) of University of Bengkulu , one of the effect was the information and data on the decline in the number of Bengkulu University's enthusiasts in public relations that was not delivered and has not become the things that need to be addressed, because public relations was not have a role as a problem solving process facilitator and communication facilitator. so, the problem of descent Bengkulu University's enthusiasts happened for last three years. However, although the public relation of University of Bengkulu only played the role of technician facilitator, the Public Relations of University of Bengkulu has successfully implemented the KIP law well, it can be seen from the awards was received from the Central Information Commission and the Regional Information Commission of Bengkulu Province.